Evaluation of Applying Urban Features Design Guides Concerning their Environmental Impact Inside Residential Complexes - Binaee Yaseen Raof (Aceh International Journal of Science and Technology, 2022)
Urban population growth has affected the spread of residential buildings in many countries. The Kurdistan region of Iraq has been witnessing rapid progress in residential complex projects. The energy consumption in buildings, especially residential buildings, is immensely affected by the design of urban open spaces around these buildings. Accordingly, this has contributed to the massive increase in energy consumption. In this paper, through analyzing previous studies, the impacts of each of the urban features of open spaces (aspect ratio, orientation of street pattern, density, and spacing ratio) on both energy consumption and outdoor thermal comfort are introduced. Also, the study is to focus on the criteria of urban features of open spaces in three existing residential projects in Sulaimani city- Iraq, by considering that there is a remarkable unawareness of the influence of urban design on microclimate and energy use. Furthermore, a direct comparison between the ratios and the optimal settings of urban features of open spaces that reduce energy consumption in buildings and achieve outdoor thermal comfort for the hot-dry climate in the context of urban open spaces in residential complexes is made. The comparison shows that the aspect ratio for two selected residential projects is below the ideal urban features ratio, and at the same time, the density and spacing ratio for all the chosen residential cities is higher than the optimal urban features ratio of open spaces in hot arid climate zone and as a result, the total loads of energy increased.